Effet bénéfique d`une combinaison de feedback, d`observation et d`imagerie motrice sur la performance du départ plongé en natation - Robin, N.; Carien, R.; Dominique, L.; Hatchi, V.; Hue, O. (Movement & Sport Sciences - Science & Motricité, 2022)
To promote performance, some coaches often use verbal feedback (FB) while others employ observation of model (OM) or motor imagery (MI: internally simulating performing an action). The purpose of this study was to test the effect of a combination of FB, OM and MI on the performance of the 25 m swim in non-experts. One hundred and six volunteer students (Mage = 19.3), randomly divided into 3 groups: FB, FB+OM and FB+OM+MI, carried out 3 phases spread over 6 sessions. Session 1 (pre-test), they carried out 5 diving starts then 25 m of swimming (filmed and timed). The following 4 sessions (8 × 25 m diving start), they received a verbal FB (every 2 trials), those of the FB+OM group also benefited from the video and those of the FB+OM+MI group imagined performing a dive after OM. Session 6 (post-test) was similar to session 1. Results showed that all the participants improved their casting speed, on the other hand only the FB+OM+MI group improved the casting distance as well as the time over 25 m. The interest of combining the methods of practice, to improve the 25 m, is discussed in the light of the literature.